Interculturalidade no Curso de Licenciatura em Música da UFRR: currículo e prática pedagógica de seus acadêmicos-docentes - Araujo, Eli de Matos (2021)
This dissertation is the result of a Master's research that aimed to understand how interculturality (QUEIROZ, 2017; WALSH, 2012) is/isn't present in the teaching practices of students from the Music Degree Course at the Universidade Federal de Roraima, who participated in the supervised internship and/orin teacher training programsas Programa Institucional de Bolsas de Iniciação à Docência (PIBID) e/ou do Programa Residência Pedagógica (PRP) and the relation these students have bounded between their teaching practices and the academic training they receive in the course. This research was draft from four specific objectives: a) to analyze the extent to which the students of the Course develop in their teaching practices a perspective of intercultural music education; b) verifying how the Pedagogical Project of the Course enables, or does not, an intercultural approach in the formation of undergraduates of the Course; c) to verify how the intercultural approach is present in the notices of teacher training programs (PIBID and PRP) for the year 2018 and d) verify how the intercultural approach is present in the Supervised Internship Regulation of the Course. The data of this research were collected from the documents referred to in the specific objectives and, in addition, also from the interviews carried out with three students from the Course, regarding the presence (or not) of interculturality in their academic-teaching practices in the teacher training activities that participated, having music as a sociocultural phenomenon(QUEIROZ, 2005). From the data analysis (BARDIN, 2011), this research brought us as an indication that: a) the analyzed documents present a majority amount of data based on cultural diversity, but when it comes to interculturality and counter-hegemonic indications, recurrences are minimal or non-existent; b) From the people interviewed's reports it can notice that the academic-teaching practices (university students) have a strong basis on the hegemonic curriculum, but with a view to pedagogical approaches that respect cultural/musical diversity, but limited in bringing it to the inside classroom debate regarding the social and cultural aspects present in the songs and c) there is an effort for interculturality to become part of the curriculum, but so far it has not been part of the academic training received by the undergraduates of the Course. Since the elements regarded in this research, the interculturality is interjected as a possibility that is still far from being part of the Course concerning the training of students who have music teaching as a tool that enables the debate on various socio-cultural issues such as prejudice, inequality and everything else able to marginalize and diminish the importance, not only of the human condition but of life as a whole in its ecosystem.